(3GdEHGfI aj Gdhba hGdGHJOGAs - (3eMeO Hf LYaQ Hf YHO GdcQje GdNRGYj , Qcf GdGSdGe CHh GdaVd,J (B408 (3g` s ((3CMeO Hf Ydi Hf CMeO Hf Nda GdCfUGQi GdeYQha HGHf GdHGPT s)
(3ChdgG (B:s
(3bGd GdTjN GdNRGYi QVi Gddg Yfg (B: (3GdMeO ddg ENdGUkG dMeOg s
(3BNQgG (B:s
(3hbGd HYVge (B: (3Ef hbaJ Ydi QCS cd BjI efgG Yf CHj YeQh hZjQg eKd Pdc ced cJGH GdEHGfI s
(3QhGjI CHj eYTQ YHO GdcQje GdebQFs
(3Yf CHj LYaQ eMeO Hf GdMSjf GdebQF GdcSGFi Yf GdeUfas
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B71 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B153s
Keywords: (3GdbQGAGJ hGdJLhjOs